Characteristics of the start in women's World Cup skeleton - Bullock, N.; Martin, D. T.; Ross, A.; Rosemond, D.; Holland, T.; Marino, F. E. (Sports Biomechanics, 2008)
This study characterizes key elements of the start in elite female World Cup skeleton athletes. The top 20 female competitors in three World Cup races were videotaped within a calibrated space to allow the following components of the start to be quantified: (1) acceleration (velocity at 15-m mark, time to 15-m mark), (2) capacity (time to load, total number of steps to load), and (3) load (velocity at 45-m mark). A correlation analysis was used to establish the relationship between the variables of interest and overall start time (15- to 65-m mark). Velocity at the 15-m mark accounted for 86% of the variance in overall start time at St. Moritz and 85% at Sigulda. A stepwise regression analysis revealed that approximately 89% of the variation in start time could be explained by velocity at the 15-m mark, time to load, and velocity at the 45-m mark. Of the variables analysed in this study, rapid acceleration to attain a high velocity at the 15-m mark was the most important component of a fast overall start time. The importance of the time to load and velocity at the 45-m mark vary according to the different track characteristics.